Pelatihan Guru Pada Daycare Halima Qur’ani Karawang - Zalfa Salsabila Nurdin; Enjang Suherman (Jurnal Ekonomi dan Bisnis Digital, 2024)
This research explains the importance of teacher training at Halima Qur'ani Daycare, a learning facility for children that provides full-day and half-day teaching and learning facilities. This study aims to understand the influences that have an impact on the learning system in daycare with teacher training which will increase productivity in the teaching and learning system. The method used is descriptive with an observative approach, students directly observe teaching and learning activities carried out at Halima Qur'ani Daycare and participate in training conducted by teachers. The mission of this educational institution is to provide integrated education with religion, to provide education by honing intellectual, emotional, spiritual and social intelligence, to provide education on a full day or half day system, to become an Islamic, characterful and trustworthy educational institution. The results of this visit show that there are service institutions that educate children from an early age.